Manajemen Bandwidth Pada Kantor Utama Distrik Navigasi Kelas 1 Menggunakan Mikrotik - Arif Ramadhani; Muhammad Taufiq Sumadi; Fendy Yulianto (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
This material discusses the implementation of bandwidth management using Queue Tree at the Samarinda Class 1 Navigation District Head Office. The internet is identified as a basic need in the operations of this government agency, especially those related to shipping safety. This activity aims to improve work efficiency and user experience through proper bandwidth management. The solution to the problem proposed is to carry out network management at the main office of the Samarinda Class 1 Navigation District using Mikrotik. The method used has 3 stages, namely design, implementation and trial. - respectively, then at the implementation stage the procedures for implementing bandwidth management will be explained step by step. The implementation results are validated through trials using a speed tester.The results of testing and design were compared, and it was found that the average difference for downloading was 1.945 while for uploading it was 1.55.